Zircon Solubility in Solute‐Rich Supercritical Fluids and Zr Transfer From Slab to Wedge in the Deep Subduction Process. Issue 9 (17th September 2021) - Chen, Wei; Xiong, Xiaolin; Takahashi, Eiichi
Abstract: Zircon solubility in aqueous fluids, hydrous melts, and supercritical fluids is important for understanding the high field strength elements (HFSEs) chemical transport in subduction zones. Although zircon solubility was extensively studied in aqueous fluids and hydrous silicate melts, its solubility in solute‐rich fluids or supercritical fluids is poorly known. Here, we experimentally determined zircon solubility in KAlSi3 O8 (±K2 O ± Al2 O3 ) – H2 O supercritical fluids at 2.0–6.0 GPa and 800°C–1000°C, close to the slab‐top conditions at sub‐arc depths. The results show that zircon solubility (expressed as ZrO2 content at zircon saturation) ranges from 65 to 6, 400 ppm ZrO2, 10–100 times higher than that in dilute aqueous fluids; it increases with temperature, solute content, and solute alkalinity (molar K/Al ratio) but decreases with pressure. The experiments at 2.0 GPa show that solute alkalinity in addition to temperature and solute content exerts a primary control on zircon solubility, while the experiments at 4.0–6.0 GPa show that the negative effect of pressure on zircon solubility is offset by the increase in solute alkalinity due to the crystallization of Al‐rich phases kyanite and muscovite. We suggest that high‐alkali supercritical fluids during deep subduction could be significant transfer agents for Zr from slab to mantle wedge. Plain Language Summary: High field strength elements (HFSEs), such as Zr, Hf, Ti, Nb, and Ta, are traditionally considered to be immobile in shallow geological processes. However, the ubiquitous presence of zircon and rutile (the hosts of HFSEs) in high‐pressure metamorphic veins and orogenic peridotites provides compelling evidence that HFSEs are transportable in subduction zones. The transfer reagents of HFSEs in subduction zones include aqueous fluids, hydrous melts, and supercritical fluids. Experimental solubility data on zircon and rutile in aqueous fluids and hydrous melts are abundant, but remain scarce in supercritical fluids, which has stymied a thorough understanding of the HFSEs transfer in subduction zones. This study experimentally determined zircon solubility in KAlSi3 O8 (±K2 O ± Al2 O3 ) – H2 O supercritical fluids at 2.0–6.0 GPa and 800–1000°C, close to the slab‐top conditions at sub‐arc depths. The results show that zircon solubility in supercritical fluids is 10–100 times higher than that in dilute aqueous fluids and increases dominantly with the solute content and alkali/Al ratio in supercritical fluids. Therefore, solute‐rich and high‐alkali supercritical fluids during deep subduction could be efficient transfer agents for Zr and other HFSEs and any models involved in chemical transfer in subduction zones should consider the role of supercritical fluids. Key Points: Zircon solubility in solute‐rich supercritical fluids is 10–100 times higher than that in dilute aqueous fluids Zircon solubility increases most prominently with the solute content and alkali/Al ratio in supercritical fluids Slab‐derived solute‐rich and high‐alkali supercritical fluids play an important role in Zr transfer in subduction zones